Strategi Pemasaran Produk UMKM melalui Digital Marketing Pada Keripik Pisang Banna-Qu - Muhammad Fajar Ramadhani (Universitas Tidar, 2021)
Marketing strategy is a process that can lead an organization/company to a large market opportunity to increase sales and achieve the desired profit. Marketing strategy is also an important tool so that companies can win the competition. Business actors often think that competitors are only a threat, but actually competitors are also a driving factor so that a company can improve its creativity and performance and build efficient and effective innovations so that it becomes a company that can be proud of the world. Digital Marketing is one of the most influential marketing media. By utilizing digital marketing in this case is social media, UMKM from Mlati Village, Mojo District, Kediri Regency are able to market home industry products in the form of banana chips. This research is a field research. This study suggests the digital marketing strategy of Banna-Qu products through the use of social media. The results of this study show that the selected social media are whatsapp, instagram, and shopee. These media are more efficient as a medium for distributing messages.